EFFECTS OF ADDING BRACKET JOINT ON RIGIDITY AND STRENGTH OF SPATIAL 3-ROD STRUCTURE OF BUS BODY - DENG TengShu; CHEN MingNian (Jixie qiangdu)
Spatial 3-rod structure is one of the bus basic structures.Effects of the topological locations of angle brackets on the rigidity and strength of spatial 3-rod structure of bus body were discussed.The calculation by finite element calculation and experimental analysis showed that:1The structural rigidity and strength under bending loads were enhanced remarkably when the plane of angle bracket was parallel to the bending loads direction.2The structural rigidity and strength under torsion loads were enhanced remarkably when angle bracket was added at the top side of the joint between the load-carrying rod and side rod.3The most effective way to enhance the structural rigidity and strength and improve its high stress distribution was adding one angle bracket at the top side of the joint between the load-carrying rod and side rod and another angle bracket at the lateral side of the joint between the load-carrying rod and master rod（ the tenth angle bracket location）.This paper provided a valuable reference to the design of agricultural machinery and engineering structures,besides the bus body joints design.